Hak Kebebasan Beragama dalam Bingkai Relatifītas Hak Asasi Manusia - Ikhwan Matondang (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
In terms of basic idea, religious freedom rights are absolute and universal. However, in terms of concept and implementation, there are diversity and distinctiveness. The right of religious freedom should not be restricted to the context of the freedom to be, but be limited in the context of the freedom to act